Chronic Regulatory Focus: Resist impulse consumption or let it happen? - Costa, Marconi Freitas da; Farias, Salomão Alencar de; Angelo, Claudio Felisoni de (Review of Business Management, 2018)
Purpose – The central objective of this research was to analyze the moderating role of chronic regulatory focus in impulse consumption when individuals are exhausted of self-control energies (ego depletion). In addition, we sought to examine the relationship between regulatory adjustment and the affective and cognitive processes of impulse decision making. Design/methodology/approach – The study was performed through an experiment. Data analysis was done using the Johnson-Neyman floodlight technique, which is recommended when the independent variable is continuous, so as not to transform it into a dichotomous variable, thus avoiding the loss of information. Findings – The results provide evidence that individuals with a profile of being vigilant about impulse decisions (focus on prevention), that is, with greater self-control in their decisions, end up spending more self-control energy than individuals who do not have this concern (focus on promotion), resulting in higher impulse consumption. Originality/value – The main contribution is a counterintuitive result that individuals who should be better prepared to withstand impulse consumption, with greater self-control, end up consuming more on impulse because they expend more energy in an attempt to control themselves.